2017
DOI: 10.1016/j.jneb.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Americans Choosing Vegetarian and Vegan Diets for Health Reasons

Abstract: Less than 2% of participants reported using a vegetarian or vegan diet for health reasons within the past 12 months. Despite potential benefits of plant-based nutrition, more research is warranted on the actual use and its effects and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
113
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 37 publications
8
113
0
6
Order By: Relevance
“…Allès et al 18 confirmed that vegetarians tend to be more educated than omnivores, but also found out that vegans tend to have lower educational attainment. Additionally, women are far more likely to be vegetarian than men 8 ; even among non-vegetarians, women have been found to eat considerably less meat than men 1,14,19,20 .Although strict and unbalanced dietary restrictions can pose a risk of micronutrient deficiencies 2 , it is the position of the Academy of Nutrition and Dietetics that appropriately planned vegetarian diets are nutritionally adequate and may be beneficial for health 21 . A comprehensive meta-analysis of 80 studies provides evidence for the link between a vegetarian diet and a lowered risk of cardiovascular disease, type 2 diabetes, obesity, and certain types of cancer 22 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Allès et al 18 confirmed that vegetarians tend to be more educated than omnivores, but also found out that vegans tend to have lower educational attainment. Additionally, women are far more likely to be vegetarian than men 8 ; even among non-vegetarians, women have been found to eat considerably less meat than men 1,14,19,20 .Although strict and unbalanced dietary restrictions can pose a risk of micronutrient deficiencies 2 , it is the position of the Academy of Nutrition and Dietetics that appropriately planned vegetarian diets are nutritionally adequate and may be beneficial for health 21 . A comprehensive meta-analysis of 80 studies provides evidence for the link between a vegetarian diet and a lowered risk of cardiovascular disease, type 2 diabetes, obesity, and certain types of cancer 22 .…”
mentioning
confidence: 99%
“…Allès et al 18 confirmed that vegetarians tend to be more educated than omnivores, but also found out that vegans tend to have lower educational attainment. Additionally, women are far more likely to be vegetarian than men 8 ; even among non-vegetarians, women have been found to eat considerably less meat than men 1,14,19,20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another category that is gaining space is the vegan public, who restricts the consumption of animal‐derived products. Veganism involves moral, ethical, spiritual or religious issues, animal welfare, health, and dietary restrictions (Cramer et al., ; Fox & Ward, ; Kessler et al., ; Ruby, ).…”
Section: Introductionmentioning
confidence: 99%
“…. animal welfare, health, and dietary restrictions (Cramer et al, 2017;Fox & Ward, 2008;Kessler et al, 2016;Ruby, 2012).…”
Section: Introductionmentioning
confidence: 99%